2022
DOI: 10.3389/fendo.2022.983180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of central obesity and associated factors in Ethiopia: A systematic review and meta-analysis

Abstract: IntroductionObesity is a global public health concern that is now on the rise, especially in low- and middle-income nations. Despite the fact that there are several studies reporting the prevalence of central obesity among adults in Ethiopia, there is a lack of a systematic review and meta-analysis synthesizing the existing observational studies. Therefore, this systematic review and meta-analysis aimed to determine the prevalence of central obesity and its associated factors in Ethiopia.MethodsOnline librarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
2
5
2
Order By: Relevance
“…Our result showed that 21.5% of patients had normal HbA1c values, suggesting good glycemic control, while 63.1% had considerably higher HbA1c levels, indicating poor glycemic control. Noteworthily, previous studies have linked suboptimal glycemic control to factors like older age, vitamin D levels, illiteracy, comorbidities, insufficient self-monitoring of blood glucose levels, insufficient physical activity, hyperlipidemia, antidiabetic drugs, longer diabetes duration, and elevated waist-to-hip ratio [15,16]. Our findings were consistent with previous local and Middle East studies that indicated poor glycemic control among individuals with T2DM based on HbA1c levels [10,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…Our result showed that 21.5% of patients had normal HbA1c values, suggesting good glycemic control, while 63.1% had considerably higher HbA1c levels, indicating poor glycemic control. Noteworthily, previous studies have linked suboptimal glycemic control to factors like older age, vitamin D levels, illiteracy, comorbidities, insufficient self-monitoring of blood glucose levels, insufficient physical activity, hyperlipidemia, antidiabetic drugs, longer diabetes duration, and elevated waist-to-hip ratio [15,16]. Our findings were consistent with previous local and Middle East studies that indicated poor glycemic control among individuals with T2DM based on HbA1c levels [10,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…At the same time, the results of this study show that the detection rate of central obesity in males is higher than that in females, which is different from available evidence [40,41]. Previous studies have shown that women are more prone to central obesity than men, which may be related to the physiological fat hoarding and different life-styles of women [26,41].…”
Section: Multilevel Logistic Regression Analysiscontrasting
confidence: 96%
“…The overall magnitude of central obesity in this study was lower than the prevalence of central obesity among public service workers in Bedele town [23], the pooled prevalence of central obesity among adult populations in Ethiopia [32], and the prevalence of central obesity among health service providers and public transportation workers in Nigeria and Peru [20,33].…”
Section: Discussioncontrasting
confidence: 64%